HUBUNGAN TERAPI OKSIGEN DENGAN INSIDEN RETINOPATHY OF PREMATURITY (ROP) PADA BAYI PREMATURE - Banin, Servasius Ratu; Saleh Nuwa, Muhammad (NHM PRESS, 2024)
This literature review aims to explore the relationship between oxygen therapy and the incidence of ROP in premature infants. A literature review was performed for this research. Literature searches both internationally and nationally use Scopus, ScienceDirect, Google Scholar, and Pubmed databases. The keywords used in the search are